"Do not impose on others what you desire." Research on the influence of service Personnel's interactive orientation on customer comfort. (March 2022) - Li, Mengyi; Ma, Qin-hai
Abstract: Comfort carries many positive consequences, and a vital issue is how to stimulate it. Because service personnel are direct service providers, which means they have a significant impact on the customer. Apparently, it is critical to improve customer comfort from the perspective of service personnel. Based on the Service Encounter theory and Regulatory Fit Theory, this paper explores how service personnel's interactive orientation, including interaction orientation, task orientation, self-orientation, influences customer comfort and examines the mediating role of perceived control and the moderating role of self-construal. We analyzed the data collected from 257 consumers using a self-reported survey using SEM with SPSS17.0 and AMOS21.0. The results show that interaction orientation has a significant positive effect on customer comfort, self-orientation has a significant negative impact on customer comfort, and task orientation has no significant impact. Perceived control plays a mediating role in the relationship between service personnel's interactive orientation and customer comfort. The moderating effect of self-construal is significant. We discussed the implications of the findings for academics and managers.